Understanding Different Geographies - Kriz, Karel.; Kriz, Karel.; Cartwright, William.; Cartwright, William.; Kinberger, Michaela.; Kinberger, Michaela. (Lecture Notes in Geoinformation and Cartography,, 2013)
This book collects revised versions of papers first delivered at the “Understanding Different Geographies Symposium” held in Puchberg am Schneeberg, Austria in 2011.  The Symposium focussed on “Communicating Meaning with [Geo]Graphic Artefacts”.  The general topics of the chapters cover: - Exploring geographic knowledge - Maps in exhibition spaces - Information and exhibition design with (geo)graphic artefacts - Extracting meaning from visualisations of different geographies - Deconstructing maps of information - and other spaces.